Pengaruh Slow Deep Breathing Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi di Wilayah Kerja Puskesmas Tiban Baru Kota Batam Tahun 2021 - Livatasia Patty; Rizki Sari Utami; Siska Natalia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hypertension is known to be a major health problem throughout the world that causes various life-threatening heart diseases. Department of Health Household Survey on Health shows that hypertension is ranked first as the most common degenerative disease. The phenomenon found in the working area of the Tiban Baru Community Health Center, Batam City in 2021 was as many as 150 people. This research was conducted to determine the effect of Slow Deep Breathing Therapy on reducing blood pressure in hypertension patients in the Tiban Baru Health Center work area, Batam City in 2021. The research method was Quasy Experimental Design, with pretest-posttest with control group. The sample consisted of 30 respondents consisting of 15 intervention group respondents and 15 control group respondents who suffered from hypertension in the Tiban Baru Community Health Center Work Area, Batam City in 2021, with a sampling technique, namely purposive sampling. Data were processed using the Wilcoxon test. The results of the study showed that the systolic blood pressure of the intervention group before treatment was 165.67 mmHg and diastole 94.73 mmHg and the systolic blood pressure of the intervention group after treatment was 155.33 mmHg and diastole 88.00 mmHg. Based on the characteristics of the respondents, it was found that the majority were >45 years old (80%), and the largest gender (73.3%) was female. The research results showed a p-value of 0.002 (<0.05). It was concluded that there was an effect of slow deep breathing on reducing blood pressure. It is hoped that hypertension sufferers can apply slow deep breathing therapy to lower blood pressure to avoid complications of hypertension.